Avaliação de ferramenta de simulação da transmissão sonora para projetos de isolamento acústico em edificações habitacionais - Silva, Renata Costa da (2014)
In July, 2013, Brazil s new standard, NBR15575:2013, began to require minimum thermal, luminal, structural and acoustical performance levels in new constructions of residential dwellings. Thus, computer programs that simulate the sound transmission in buildings, can serve as important tools for professionals, enabling the verification of virtual acoustic performance of projects, quickly and economically. By being widely used in European countries, they have the database of existing elements and building systems in Europe. From this, this study aimed to evaluate a computational tool of simulation of sound transmission on the reality of Brazilian buildings. Twenty households were selected in the city of Santa Maria - RS, to be measured in situ and then simulated to airborne and impact noise. The residences were chosen according to standard and types of building systems. For greater representation of Brazilian buildings, residences of low, medium and high standards were chosen. The building systems chosen were structural masonry, structural walls with concrete or ceramic block; and reinforced concrete, with walls of hollow brick; all with massive concrete slab. The software used for the simulations was the SONarchitect and all the features and building elements used were entered into the software s database. The values of Ln,T , Dn,T , and RT per frequency band, and their weighted values Ln,T,w, Dn,T,w and mean RT were obtained through measurements and simulation. The weighted measured and simulated values were similar, on the other hand, the values obtained by frequency band showed disagreement with the lower frequencies precisely, from 50 Hz to 100 Hz. There was also a relationship of impact sound transmission loss with the area size of the partition, in which there is a significant increase in sound insulation in partitions with larger areas. In addition, coefficients and safety factors were determined for each standard and building system to be applied in the spectra of the simulations, aiming to bring the simulated values closer to the measured ones. Parallel with the evaluation of the computational tool, questionnaires with 150 professionals who develop acoustic projects in the country were applied. This step had as main objective to find out what tools and methods are mostly used by professionals in the development of these projects. From 31 received responses, it was determined that 20.88% of the professionals use a computational tool to develop designs. It was also possible to discover some features such as field of expertise and graduation year, which regions they are located, what kind of projects they develop and if they have already developed projects based on the new standard.